Self‐consistent generation of single‐plume state for Enceladus using non‐Newtonian rheology. Issue 3 (4th March 2014) - Rozel, A.; Besserer, J.; Golabek, G. J.; Kaplan, M.; Tackley, P. J.
Abstract The thermal dichotomy of Enceladus suggests an asymmetrical structure in its global heat transfer. So far, most of the models proposed that obtained such a distribution have prescribed an a priori asymmetry, i.e., some anomaly in or below the south polar ice shell. We present here the first set of numerical models of convection that yield a stable single‐plume state for Enceladus without prescribed mechanical asymmetry. Using the convection code StagYY in a 2‐D spherical annulus geometry, we show that a non‐Newtonian ice rheology is sufficient to create a localized, single hot plume surrounded by a conductive ice mantle. We obtain a self‐sustained state in which a region of small angular extent has a sufficiently low viscosity to allow subcritical to weak convection to occur due to the stress‐dependent part of the rheological law. We find that the single‐plume state is very unlikely to remain stable if the rheology is Newtonian, confirming what has been found by previous studies. In a second set of numerical simulations, we also investigate the first‐order effect of tidal heating on the stability of the single‐plume state. Tidal heating reinforces the stability of the single‐plume state if it is generated in the plume itself. Lastly, we show that the likelihood of a stable single‐plume state does not depend on the thickness of the ice shell.